Financial Distress Analysis of Textile and Garment Companies Listed on the Indonesian Stock Exchange - Burhanuddin; Rasmi Nur Anggraeni; Mohammad Rahul Syaifullah; Farid; Guasmin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Results study this shows that several company textiles And garments are listed on the IDX with sound performance and bad. No, there is a company with good performance finance. A company that owns performance fewer finances Good in the category vulnerable is Sunson Textile Manufacture Tbk And Trisula International Tbk. This company, on average, on the position of Gray Area (prone) or is in between the range of 1.81 to 2.99. A company that owns bad performance finances (bankruptcy) or experience difficulty financially (financial distress) are PT Panasia Indo resources Tbk, Asia Pacific Investama Tbk, Ricky Putra Globalindo Tbk, and Star Petrochem Tbk. This company's average value is under 1.81, which is limited from the category performing company finance badly (broke). Furthermore, researchers can add or compare the author's analysis model use with other analytical models related to the method Altman Z-Score so that they can analyze giving problems results And input to the company.